Exploratory Study of the Potential of the National Library as a Tourism Destination Based on Library tourism - Yudian, Rais A; Ingkadijaya, Rahmat; Ratu Balqis, Linda Desafitri (Jurnal Toursci, 2025)
Background. Libraries today are not just a place to find and store information. Libraries have developed into one of the most sought-after tourist destinations when visiting a place. Aims. This research was conducted to identify and analyze the attractiveness and application of the concept. This research uses a qualitative approach with a triangulation analysis method. Result. One of the libraries that many tourists now visit for recreation and tourism purposes is the National Library of the Republic of Indonesia. The development of the National Library is progressing rapidly and has become an attraction in its own right. Therefore, to support the National Library as a tourist destination, one approach that can be applied is library tourism. This approach can be implemented if the manager plays their role well. Conclusion. The results showed that the National Library has a variety of attractions and has implemented the concept of library tourism. Implementation. The description led the researcher to conduct research at the National Library of Indonesia related to the implementation of library tourism.